GhWRKY75 positively regulates GhPR6-5b via binding to a W-box TTGAC (C/T) to orchestrate cotton resistance to Verticillium dahliae - Qichao Chai; Meina Zheng; Yanli Li; Mingwei Gao; Yongcui Wang; Xiuli Wang; Chao Zhang; Hui Jiang; Ying Chen; Jiabao Wang; Junsheng Zhao (Journal of Integrative Agriculture)
Verticillium dahliae is an important fungal pathogen affecting cotton yield and quality. Therefore, the mining of V. dahlia-resistance genes is urgently needed. Proteases and protease inhibitors play crucial roles in plant defense responses. However, the functions and regulatory mechanisms of the protease inhibitor PR6 gene family remain largely unknown. This study provides a comprehensive analysis of the PR6 gene family in the cotton genome. We performed genome-wide identification and functional characterization of the cotton GhPR6 gene family, which belongs to the potato protease inhibitor I family of inhibitors. Thirty-nine PR6s were identified in Gossypium arboreum, G. raimondii, G. barbadense, and G. hirsutum, and they were clustered into four groups. Based on the analysis of pathogen-induced and Ghlmm transcriptome data, GhPR6-5b was identified as the key gene for V. dahliae resistance. Virus-induced gene silencing experiments revealed that cotton was more sensitive to V. dahliae V991 after PR6-5b silencing. The present study established that GhWRKY75 plays an important role in resistance to Verticillium wilt in cotton by positively regulating GhPR6-5b expression by directly binding to the W-box TTGAC(T/C). Our findings established that GhWRKY75 is a potential candidate for improving cotton resistance to V. dahliae, and provide primary information for further investigations and the development of specific strategies to bolster the defense mechanisms of cotton against V. dahliae.